Beta-blockers provide a differential survival benefit in patients with coronary artery disease undergoing contemporary post-percutaneous coronary intervention management - Pil Hyung Lee (Nature Portfolio, 2020)
Abstract Beta-adrenergic receptor blockers are used in patients with coronary artery disease (CAD) to reduce the harmful effects of excessive adrenergic activation on the heart. However, there is limited evidence regarding the benefit of beta-blockers in the context of contemporary management following percutaneous coronary intervention (PCI). We used the nationwide South Korea National Health Insurance database to identify 87,980 patients with a diagnosis of either acute myocardial infarction (AMI; n = 38,246) or angina pectoris (n = 49,734) who underwent PCI between 2013 and 2017, and survived to be discharged from hospital. Beta-blockers were used in a higher proportion of patients with AMI (80.6%) than those with angina (58.9%). Over a median follow-up of 2.2 years (interquartile range 1.2–3.3 years) with the propensity-score matching analysis, the mortality risk was significantly lower in patients treated with a beta-blocker in the AMI group (HR: 0.78; 95% CI 0.69–0.87; p < 0.001). However, the mortality risk was comparable regardless of beta-blocker use (HR: 1.07; 95% CI 0.98–1.16; p = 0.10) in the angina group. The survival benefit associated with beta-blocker therapy was most significant in the first year after the AMI event.